Expanding and Improving Early Childhood Education in Turkey - World Bank (Washington, DC, 2013)
Over the past decade, Turkey has experienced significant socioeconomic progress and demographic changes. The benefit of Early Childhood Education (ECE) programs is maximized when the interventions are targeted to children from disadvantaged families. This report examines the ECE provision in Turkey, and offers policy options for improving and expanding the ECE system in the future. The report endorses the goal of the expansion plan and provides detailed recommendations for achieving this ambition in an efficient and equitable manner. This report is divided into following four sections: section one gives introduction, section two presents an analytical framework for analyzing early childhood interventions, section three conducts an in-depth analysis of ECE in Turkey and identifies key challenges, and section four recommends and outlines proposals for a dual-program strategy for expanding quality ECE in Turkey.